Aktanten im Gesundheitswesen? KI-Systeme aus der Perspektive technischer Vermittlung = Actants in the Healthcare Sector? AI Systems through the Lens of Technical Mediation - Hahn, Michael (Zeitschrift für medizinische Ethik, 2025)
AbstractThis contribution examines how the changes brought about by the use of AI in healthcare can be precisely captured and theoretically contextualized. Drawing on Actor-Network Theory (ANT) and the concept of technical mediation, it shows how reconfigurations of agency can be systematically analyzed (composition). In addition, goal realignments (translation) as well as new challenges regarding transparency (reversible blackboxing) and responsibility (delegation) become clearly apparent with AI agents and agentic AI., AbstractThis contribution examines how the changes brought about by the use of AI in healthcare can be precisely captured and theoretically contextualized. Drawing on Actor-Network Theory (ANT) and the concept of technical mediation, it shows how reconfigurations of agency can be systematically analyzed (composition). In addition, goal realignments (translation) as well as new challenges regarding transparency (reversible blackboxing) and responsibility (delegation) become clearly apparent with AI agents and agentic AI.